Du lyrisme au lecteur : le désir de contemporanéité chez João Cabral et Ana Cristina Cesar - Marcos Siscar (Brésil(s))
This article proposes a reading of João Cabral de Melo Neto's essays, in particular « Poesia e composição », highlighting the concepts of « norm » and « reader ». The aim is to understand how the notion of compositional objectivity implies a political concern related to the critical nature of poetry. Ana Cristina Cesar's re-reading of some of these elements suggests that the debate on lyricism has served to make explicit the tasks that post-avant-garde poetry has set itself in Brazil in order to redefine its historical role.